الوحدات التدريبية في تطوير القوة الانفجارية للاطراف السفلى لدى لاعبات كرة الطائرة 15سنة - عيبوط فريال (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
هدف البحث الى دراسة تاثير الوحدات التدريبية لتطوير صفة القوة الانفجارية الأطراف السفلى لدى لاعبات كرة الطائرة و قد استخدمت الطالبة المنهج التجريبي لملائمته لمشكلة البحث و قد بلغت العينة 11 لاعبة في العينة الضابطة و 11 لاعبة في العينة التجريبية من فئة أقل من 15 سنة لفريق الإتحاد الهاوي للتحدي لاعبات لكرة الطائرة بلدية المحمدية و تم تنفيد البرنامج التدريبي على مدى فترة زمنية محددة 7 أسابيع و لأجل تنفيذ خطوات البحث اختارت الباحثة اختبارين لقياس القوة الانفجارية اختبار الوثب العمودي سارجنت و اختبار الوثب العريض من الثبات التي تخدم أهداف البحث و قد أظهرت نتائج العينة التجريبية تحسنا ملحوظا و بعد تحليلها و مناقشتها مما يدل على فعالية هده الوحدات التدريبية في تعزيز الأداء البدني المرتبط بالقوة الانفجارية و هو عنصر أساسي في رياضة كرة الطائرة. // // // // // // The aim of the research was to study the effect of training units to develop the explosive strength of the lower extremities of female volleyball players. The researcher used the experimental method to suit the research problem. The sample amounted to 11 players in the control sample and 11 players in the experimental sample from the under-15 category of the amateur team for the challenge of female volleyball players in the municipality of Mohammedia. The training program was implemented over a specific period of 7 weeks. In order to implement the research steps, the researcher chose two tests to measure explosive strength: the Sargent vertical jump test and the standing broad jump test, which serve the research objectives. The results of the experimental sample showed a noticeable improvement after analysis and discussion, which indicates the effectiveness of these training units in enhancing physical performance related to explosive strength, which is an essential element in volleyball.
LES-2025-21
Keywords: الوحدات التدريبية; القوة الانفجارية; الاطراف السفلى; لاعبات كرة الطائرة 15سنة